PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIK MAHASISWA PGSD MELALUI PENERAPAN MODEL PEMBELAJARAN CIRC - Ratih Purnamasari; Jaja Sudarjat (Universitas Pakuan, 2021)
IMPROVEMENT OF MATHEMATIC COMMUNICATION SKILLS FOR PGSD STUDENTS THROUGH THE APPLICATION OF CIRC LEARNING MODELSMathematical communication skills are very important to be mastered by a prospective teacher. Without this ability it is impossible for him to be able to guide his students, especially in mathematics. In addition, they also have to teach their students mathematical communication skills. However, the data prove that students' communication skills are still low. They are not yet able to express their ideas orally or in writing. This study aims to see if there are differences in communication skills through the application of the CIRC learning model with the conventional learning model. The method used is a two-class quasi experiment. The instrument used is a test description which requires answers that show mathematical communication skills. Data analysis was performed by testing the hypothesis using statistical techniques t test. For the real level of 5% or 0.05 with the value dk = (n1 + n2 - 2) = 47, then the t table shows the number 2.01174. From the t test carried out, it was obtained t_ (count) of 6,527. Because t_ (count) ttable, H_ad is accepted and H_ (0) is rejected. So it can be concluded that there are differences in students' communication skills through the application of the CIRC model with conventional learning models. The CIRC Learning Model is considered to be better in improving student communication skills